Dopamine D2 Receptor as a Cellular Component Controlling Nocturnal Hyperactivities in Drosophila melanogaster. (2013) - Lee, Gyunghee; Kikuno, Keiko; Bahn, Jae-Hoon; Kim, Kyeong-Man; Park, Jae H.
Abstract : Dysfunctional regulation of brain dopamine (DA) functions has been found in patients with drug addiction and various neurological disorders that frequently accompany disturbance in sleep behavior. In this study, the roles of the dopaminergic nervous system on the regulation of daily locomotor activity rhythm were investigated in Drosophila melanogaster . Reduced synaptic DA release by expressing tetanus toxin gradually attenuated peak activity levels by altering activity patterns, particularly under constant darkness. Besides, flies with a mutant dopamine transporter fumin ( fmn ), in which the synaptic DA levels were elevated, displayed increased activities in both daytime and nighttime, but did more so at nighttime, suggesting that DA function is involved in regulation of fruit fly's nocturnal locomotor activities. Furthermore, flies treated with bromocriptine, an agonist of Drosophila dopamine D2 receptor (dD2R), exhibited nocturnal locomotor hyperactivity in a dose-dependent manner and this effect was inhibited in dD2R knockdown flies. When mutant flies null for period ( per ), timeless ( tim ), dClock ( dClk ), or cycle ( cyc ) were treated with bromocriptine, only cycle -null flies ( cyc 01 ) did not show induced nocturnal hyperactivities, suggesting that cyc might play a role in bromocriptine-induced nocturnal hyperactivities. Elevation of experimental temperature also increased nocturnal activities at the expense of daytime activities. The heat-induced increase in nocturnal activities gradually returned to basal levels at continuously elevated temperature. Inhibition of DA synthesis did not suppress heat-induced early development of nocturnal hyperactivity but prevented gradual decrement of initially elevated nocturnal activities, suggesting that DA impinges on certain adaptive roles in response to changes in environmental temperature. These results overall suggest that controlling dopaminergic transmission is important for daily locomotor behavior and bromocriptine-induced nocturnal hyperactivity which is mediated through dD2R receptor and CYC functions. In parallel to these results, excessive activation of dopaminergic neurotransmission, the primary cause of schizophrenia, is associated with abnormally elevated nocturnal locomotor activities through D2-type receptor in Drosophila . The results suggest that fruit flies are an excellent model system to provide some answers to previously unexplainable observations regarding the compromised dopaminergic nervous system and the related therapeutic agents. (Author correspondence:kmkim@jnu.ac.kr )